Design, Synthesis, in silico and in vitro antibacterial studies and molecular docking analysis of novel Benzotriazole derivatives - Aggarwal, Nishu; Singh, Navneet; Kaur, Harleen; Kaur, Gurmeet (Journal of Neonatal Surgery, 2025)
Heterocyclic Chemistry plays an important role in medicinal chemistry. Benzo-condensed compounds containing hetero atoms have been extensively studied for their biological activities. So, it was aimed to synthesize biological active compounds with high potency, lower toxicity and enhanced action mechanism. The present research work deals with the study of ADMET, synthesis, molecular docking and in-vitro antimicrobial activities. All the synthesized compounds were well characterized using various spectroscopic techniques. Further, the compounds were screened for antimicrobial activities and moreover these synthesized compounds along with standard drug Amoxicillin were docked with crystal structure of S. aureus TarS with PDB ID 5TZ8. Based on in vitro and in silico studies in comparison to amoxicillin as standard reference drugs, compound 2a has revealed efficient results towards selected bacterial and strains